2005
DOI: 10.1117/12.600360
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field ion mitigation for EUV light sources

Abstract: Fast ions from laser-produced EUV plasma are expected to significantly damage the collector mirror, which is located near the plasma in a EUV light source. Ion sputtering of the multilayer structure may be the main damage mechanism but layer boundary mixing and surface roughness increase are also observed from a Xe plasma exposure experiment. The magnetic field ion mitigation technology was evaluated in order to extend the collector mirror lifetime. A coil pair that produces a maximum static magnetic field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…16 The effectiveness of the magnetic field ion mitigation was evaluated by measuring the erosion rate with a quartz crystal microbalance. 21 A significant decrease of the Faraday cup (FC) signal was monitored by applying a magnetic field of 0.6 T. Target size dependence on magnetic field effectiveness was observed, measured erosion rate was reduced to less than 10% by applying 0.6 T magnetic field in the case of 10-lm Xe jet and 300-mJ Nd:YAG laser irradiation. 21 It was shown that with Nd:YAG laser and Sn rod target the fast ion signal decreased to <0.1% with 1 T magnetic flux density.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…16 The effectiveness of the magnetic field ion mitigation was evaluated by measuring the erosion rate with a quartz crystal microbalance. 21 A significant decrease of the Faraday cup (FC) signal was monitored by applying a magnetic field of 0.6 T. Target size dependence on magnetic field effectiveness was observed, measured erosion rate was reduced to less than 10% by applying 0.6 T magnetic field in the case of 10-lm Xe jet and 300-mJ Nd:YAG laser irradiation. 21 It was shown that with Nd:YAG laser and Sn rod target the fast ion signal decreased to <0.1% with 1 T magnetic flux density.…”
Section: Introductionmentioning
confidence: 98%
“…21 A significant decrease of the Faraday cup (FC) signal was monitored by applying a magnetic field of 0.6 T. Target size dependence on magnetic field effectiveness was observed, measured erosion rate was reduced to less than 10% by applying 0.6 T magnetic field in the case of 10-lm Xe jet and 300-mJ Nd:YAG laser irradiation. 21 It was shown that with Nd:YAG laser and Sn rod target the fast ion signal decreased to <0.1% with 1 T magnetic flux density. 22 Experiments with Nd:YAG laser irradiation on Tin target showed that the kinetic energies of the plume species were considerably reduced even at short distances with a modest perpendicular magnetic field of 0.64 T. 23 Confinement and dynamics of laser-produced plasma expanding across a transverse magnetic field has been studied by many authors, [24][25][26][27][28][29] however, there are a very few a) Electronic addresses: roy@fzu.cz and aroy@barc.gov.in reports available for dynamics of plasma expanding along the direction of the magnetic field.…”
Section: Introductionmentioning
confidence: 98%
“…13 Several studies have been conducted to devise new or to improve upon existing schemes to mitigate and/or decrease debris emission such as: mass-limited targets, 18,19 ambient gases, 20,21 and magnetic confinement. 19,22 Currently radiation from both Nd:YAG and CO 2 lasers are considered to be promising excitation sources for producing Sn plasmas and hence significant efforts are going into optimizing laser and target parameters to develop efficient and clean EUV light source. Hence it is imperative to have a detailed account of ion and neutral particle emission from these plasmas for developing efficient debris mitigation schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mitigation of the debris is of importance for the development of a practical EUV lithography system. Although several methods have been developed for the debris mitigation [5][6][7], the fundamental and general approach is the use of a minimum amount of Sn that can still provide a sufficient EUV power. This type of Sn target is called a mass-limited or a minimum-mass target [8][9][10].…”
Section: Introductionmentioning
confidence: 99%